(3agQSJ JGQjN OeTb GdTGes - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3NWHI GdcJGH HGH ai PcQ CUd ETJbGb JSejI GdTGe Yf GdYGdejf HGdfbd hGdYGQajf HCUhd GdcdGe s
(3BNQgG (B:s
(3HGH ai EeQCg TGYQI ef fUGQi HUQi s
(3HgG fXGe GdJYbjHIs
(3HChdg agQSJ ddcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs